2019
DOI: 10.1021/acs.organomet.9b00425
|View full text |Cite
|
Sign up to set email alerts
|

E-Selective Synthesis and Coordination Chemistry of Pyridine-Phosphaalkenes: Five Ligands Produce Four Distinct Types of Ru(II) Complexes

Abstract: Pyridine-phosphaalkene (PN) ligands 2a−e were prepared in an E-selective fashion using phospha-Wittig methodology. Treatment of these five ligands, varying only in their 6-substituent with RuCl 2 (PPh 3 ) 3 , produced four distinct types of coordination complexes: pyridine-phosphaalkenederived 3b,d, cyclized 4e, and six-coordinate 5a and 6c. Prolonged heating of 3b,d in THF resulted in C−H activation of the Mes* group and cyclization to give 4b,d featuring a bidentate pyridine-phospholane ligand bound to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Despite the established π-accepting character of PC ligands, the PC bond length of the E - 1a ligand does not change upon coordination to Au I . This has been attributed to a rehybridization of the P-center whereupon the P–C σ-bonds have increased s -character in the complex, thereby giving a shorter σ-bond which cancels out the lengthening due to π-acceptance. This rehybridization appears to be supported by the observed increase in the Mes*PC angle in [Au­( E - 1a )­Cl] [108.23(14)°] compared to E - 1a [103.4(2)°] and a shortening of the Mes*–P bond {[Au­( E - 1a )­Cl]: 1.822(3); E - 1a 1.860(4) Å}. The P(1)–Au(1) bond length [2.2228(8) Å] is in the range expected for related phosphaalkene-Au I complexes [2.20(5) to 2.242(11) Å] …”
Section: Resultsmentioning
confidence: 96%
“…Despite the established π-accepting character of PC ligands, the PC bond length of the E - 1a ligand does not change upon coordination to Au I . This has been attributed to a rehybridization of the P-center whereupon the P–C σ-bonds have increased s -character in the complex, thereby giving a shorter σ-bond which cancels out the lengthening due to π-acceptance. This rehybridization appears to be supported by the observed increase in the Mes*PC angle in [Au­( E - 1a )­Cl] [108.23(14)°] compared to E - 1a [103.4(2)°] and a shortening of the Mes*–P bond {[Au­( E - 1a )­Cl]: 1.822(3); E - 1a 1.860(4) Å}. The P(1)–Au(1) bond length [2.2228(8) Å] is in the range expected for related phosphaalkene-Au I complexes [2.20(5) to 2.242(11) Å] …”
Section: Resultsmentioning
confidence: 96%
“…According to 1 H NMR spectroscopy, the phosphaalkene moieties adopt an E -configuration with the PCH proton showing the expected doublet at 8.25 or 8.60 ppm, respectively, and a 2 J P–H coupling constant of approximately 25 Hz (cf. E -configured P,N-phosphaalkene ligands 2 J P–H = ca. 25 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from Geoffroy’s studies of a pyridine-based P,N-phosphaalkene Cu complex, a series of Ru P,N-phosphaalkene complexes were reported by Cain and co-workers just recently. The latter complexes showed intramolecular C–H bond activation at the Mes* groups to produce phosphaindane structures (Scheme (bottom left)) . Similarly, Ozawa and co-workers showed that using the related Mes*-substituted P,N,P-type ligand, twofold cyclization occurred to give the corresponding bis-phospholanyl RhCl-complex (Scheme (bottom right)) .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation